Maximising engagement and participation of intellectual disability staff in research: Insights from conducting a UK-wide survey. (December 2021) - Lam, Claire Kar Kei; Bernal, Jane; Finlayson, Janet; Todd, Stuart; Taggart, Laurence; Boaz, Annette; Tuffrey-Wijne, Irene
Aim: This article explores ways of maximising engagement of intellectual disability staff as research participants, research advisers and research implementers. Method: The authors describe and reflect on a three-phased strategy in recruiting front-line staff ( n = 690) working for intellectual disability service providers ( n = 25) to participate in a UK-wide anonymous online survey about death, dying and bereavement. Results: Important elements in engaging participants were: involving stakeholders at all stages of the research process, which includes: building relationships with participating organisations; enlisting organisational management support at all levels; an attractive and well laid-out collection tool; a well-structured recruitment strategy; time and flexibility; and a varied and targeted dissemination strategy. However, the recruitment method had limitations, in particular around representativeness, bias and generalisability. Conclusions: Staff in intellectual disability services can be enthusiastic and invaluable research participants. Active engagement between researchers, participating organisations and stakeholder groups is key to ensuring involvement of intellectual disability staff with research.